La reforma agraria en Costa Rica (1962-2002): balance de las intervenciones estatales en el cantón de Osa - Royo Aspa, Antoni (2003)
This article addresses the agrarian reform developed by the Costa Rican government between 1962 and 2002 in the canton of Osa. This process was institutionalized through the Costa Rican Institute of Land and Settlement (lTCO by its Spanish acronym), later known as Agrarian Development Institute (IDA). With the use of census and institutional data, the author carries out a critical analysis of "Costa Rican- style agrarian reform" as a result of this study case.